2022
DOI: 10.1037/per0000537
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a hierarchical dimensional structure of high experiential permeability: A bass-ackward approach to linking positive schizotypy and openness to experience.

Abstract: Research on dimensional models of personality pathology has achieved a good deal of consensus on the 5 broad constructs that span adaptive and maladaptive personality traits. Nonetheless, connections between the 5th domain, typically called openness to experience within general personality measures and psychoticism or schizotypy on maladaptive measures, have proven more challenging to integrate. Using experiential permeability as a guiding framework, the current study seeks to develop a hierarchical, empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…First, neither Openness (O) nor Psychoticism (PSY) had any notable cross-measure correlations in either type of study: PSY correlated mostly strongly with self-reported Neuroticism (N; r = .30), whereas O correlated mostly strongly with PSY (r = .20 in both types of studies). These results are relevant to the ongoing debate regarding relations between these two constructs (Blain et al, 2020;Bucher & Samuel, 2021;Widiger & Crego, 2019). Second, not surprisingly, relations between the PID-5 and non-self-report ratings are somewhat lower than those between the two sets of self-report scales: Omitting PSY/O, the average same-versus cross-method convergent correlations are .71 and .58, respectively.…”
Section: Domain-level Structurementioning
confidence: 76%
“…First, neither Openness (O) nor Psychoticism (PSY) had any notable cross-measure correlations in either type of study: PSY correlated mostly strongly with self-reported Neuroticism (N; r = .30), whereas O correlated mostly strongly with PSY (r = .20 in both types of studies). These results are relevant to the ongoing debate regarding relations between these two constructs (Blain et al, 2020;Bucher & Samuel, 2021;Widiger & Crego, 2019). Second, not surprisingly, relations between the PID-5 and non-self-report ratings are somewhat lower than those between the two sets of self-report scales: Omitting PSY/O, the average same-versus cross-method convergent correlations are .71 and .58, respectively.…”
Section: Domain-level Structurementioning
confidence: 76%
“…Although there is no clear consensus regarding necessary sample sizes for exploratory factor analyses, samples larger than 400 participants appear sufficient. This rationale is based on the current study's communality of explored constructs and its focus on a single, overarching construct (MacCallum et al, 1999) along with the fact that each sample in this study is similar to or larger than previously published empirical investigations that implemented ‘bass‐ackward’ analytic approaches (e.g., Billen et al, 2022; N s = 200, 118, 94; Bucher & Samuel, 2022; N = 406). The examination of the replicability of these results across two independent samples also provides some safeguard against fears that smaller samples might yield more idiosyncratic results.…”
Section: Methodsmentioning
confidence: 99%